Diagnostic value of anti-nucleosome antibodies in systemic lupus erythematosus and other connective tissue diseases - Szewczyk, Agnieszka; Kołacińska-Strasz, Zofia; Gliński, Wiesław (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Anti-nuclear antibodies are autoantibodies to many nuclear and cytoplasmic antigens. They are present in a proportion of patients with various connective tissue diseases (CTD) and some of them are regarded as their immunological markers. In recent years some reports on the diagnostic and prognostic value of anti-nucleosome antibodies have been published. Nucleosomes are part of chromatin, consisting of histones around which is wrapped a stretch of DNA. Nucleosomes are released in the process of cell apoptosis. Antibodies to nucleosomes have been found in sera of patients with: SLE, localized and systemic scleroderma, MCTD, and dermatomyositis, as well as in primary antiphospholipid syndrome and in patients treated with anti-TNF-α biologicals. Objective. Analysis of the diagnostic value of anti-nucleosome antibodies in various CTD, especially in SLE, and their correlation with antinuclear antibodies of other specificities and clinical findings. Material and methods. The material comprises 74 sera of patients with various CTD (25 – localized scleroderma, 19 – SLE, 13 – Sjögren’s syndrome, 8 – polymyositis, 12 –scleromyositis), positive for antinuclear antibodies in the indirect immunofluorescence test on HEp2 cells. Detection of anti-nucleosome antibodies and identification of specificity of other ANA were performed using the EUROLINE test (Euroimmun Medizinische Labordiagnostika Lubeck AG, Germany). Results. Antibodies to nucleosomes were found in 7 out of 19 (37%) sera of patients with SLE and in 1 of 25 sera (4%) of patients with localized scleroderma. In 5/7 cases of SLE anti-nucleosome antibodies coexisted with dsDNA and Ro antibodies. In one patient with SLE, anti-nucleosome antibodies were the only antibodies found. The majority of patients with SLE with anti-nucleosome antibodies have had renal involvement. Conclusions. Our preliminary results allow us to suppose that antibodies to nucleosomes may be a valuable immunological marker of SLE, especially of lupus nephritis.